Respuesta :

Answer:

3. 5

5x • y I am pretty sure this is the answer. The exponents might be wrong.

Step-by-step explanation:

7 8

10x y 3 5

———- x ————- = 5x • y

4 3

2x y

Answer:

see explanation

Step-by-step explanation:

Using the rules of exponents

[tex]a^{m}[/tex] × [tex]a^{n}[/tex] ⇔ [tex]a^{(m+n)}[/tex]

[tex]\frac{a^{m} }{a^{n} }[/tex] ⇔ [tex]a^{(m-n)}[/tex]

(5)

Split the factors into like terms

= [tex]\frac{10}{2}[/tex] × [tex]\frac{x^{7} }{x^{4} }[/tex] × [tex]\frac{y^{8} }{y^{3} }[/tex]

= 5 × [tex]x^{(7-4)}[/tex] × [tex]y^{(8-3)}[/tex]

= 5x³[tex]y^{5}[/tex]

(6)

Consider the left side

[tex]\frac{y^{(4+n)} }{y^2}[/tex] = [tex]y^{(4-2+n)}[/tex] = [tex]y^{2+n}[/tex], then

[tex]y^{2+n}[/tex] = [tex]y^{-3}[/tex]

Since the base on both sides is y, equate the exponents

2 + n = - 3 ( subtract 2 from both sides )

n = - 5

ACCESS MORE